Treinamento auditivo formal em adultos com deficiência auditiva - Gil, Daniela [UNIFESP] (2006)
Objective: To verify the effects of a formal auditory training program in adult hearing aid users with mild to moderate sensorineural hearing loss using behavioral auditory processing tests, a self-report benefit scale and long latency auditory evoked potential – P300. Method: Fourteen intra-aural hearing aid users were divided into two groups: seven with auditory training and seven without auditory training. Subjects from experimental group have undergone a formal auditory training program with hearing aids, organized in eight sessions of 45 minutes each, twice a week, aiming at improving auditory closure, figure-to-ground for verbal and nonverbal sounds and temporal processing (frequency and duration of sounds) skills. The program itself and the activities within the session were proposed in progressive complexity in order to challenge the auditory system. Auditory training efficiency was verified by evaluating all subjects in two different occasions: pre and post-training in the Experimental Group and in the initial and final evaluations in the Control Group, including electrophysiologic and behavioral auditory processing evaluations and the application of the self-report benefit scale APHAB. Results: Neither amplitude and latency of P300 nor the behavioral central auditory tests used revealed significant differences for the right or left ears. In the post-training evaluation Experimental Group presented statistically significant reduction in P3 latency, improved performance in all behavioral auditory processing tests and higher benefit in noisy situations as demonstrated in the self-report benefit scale APHAB than the Control Group. Conclusions: We could conclude that formal auditory training in adult hearing aid users lead to reduction in P3 latency; improvements in memory for verbal and nonverbal sounds in sequence, auditory closure, figure-to-ground for verbal sounds and higher benefit in reverberant and noisy environments